Slums Prevention from A Policy Perspective in Indonesia - Maman Sukiman; Deva Fosterharoldas Swasto (UNIFIKASI : Jurnal Ilmu Hukum, 2022)
Many studies on aspects of slums area improvement and the causes of slums settlements have been carried out, but studies that focus on aspects of slums prevention are still challenging to find. One reason for the emergence of slums is the Government's failure of policies and their implementation. This article aims to examine the prevention of slums settlements in the policy perspective of Law Number 1 of 2011 concerning Housing and Settlements Areas and the Regulation of the Minister of Public Works and Public Housing Number 14/PRT/M/2018 concerning Prevention and Quality Improvement of Slums. They are analyzed using a qualitative method with a normative juridical approach. The results of the analysis show that the slums prevention policy has several weaknesses; namely, prevention policy should start from planning not directly to control and supervision, slums prevention settlements is still focused on urban areas, slums prevention is not considered urgent, and there are some biases in the prevention of slums measurement of slums criteria which has the potential to make the policy of preventing slums settlements, not on target. For these reasons, the Government needs to make policies that are more operational in preparing plans of slums prevention; considering aspects of the causes of slums in policymaking; synergizing slum area improvement policies with slum prevention policies; campaigning for the importance of preventing slum in both urban and rural areas; refining slums criteria or indicators; involving stakeholders in the formulation and implementation of slum prevention policies; and increasing community social capital.